Moving Out of the Comfort Zone: How Cultural Norms Affect Attitudes toward Immigration - Yvonne Giesing; Björn Kauder; Lukas Mergele; Niklas Potrafke; Panu Poutvaara (Institute of Labor Economics (IZA), 2024)
We examine how cultural norms shape attitudes toward immigration. Our causal identification relies on comparing students who moved across the East-West border after German reunification with students who moved within former East Germany. Students who moved from East to West became more positive toward immigration. Results are confirmed among students whose move was plausibly exogenous due to national study place allocation mechanisms. Evidence supports horizontal transmission as the difference between East-West movers and East-East movers increases over time and is driven by East German students who often interacted with fellow students. Effects are stronger in less xenophobic West German regions.
Keywords: D72; D91; J15; J20; P20; P51; Z10; 330; cultural transmission; migration; attitudes toward immigration; German division and unification; political socialization